2021
DOI: 10.1016/j.xphs.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Budding-Like Intestinal Organoids from Human Induced Pluripotent Stem Cells

Abstract: Human induced pluripotent stem (iPS) cell-derived intestinal organoids have low invasiveness; however, the current differentiation method does not reflect the crypt-villus-like structure due to structural immaturity. Here, we generated budding-like organoids that formed epithelial tissue-like structures and had the characteristics of the mature small intestine from human iPS cells. They showed a high expression of drug transporters and induced the expression of cytochrome P450 3A4 and P-glycoprotein. When trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Human iPS cells (Windy) were cultured as reported previously [ 24 , 25 ]. A modified version of a previously described differentiation protocol for induction at day 7 was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human iPS cells (Windy) were cultured as reported previously [ 24 , 25 ]. A modified version of a previously described differentiation protocol for induction at day 7 was used.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, 3D-organoids are not suitable research tools for drug absorption and transport studies. To overcome this drawback, we recently established a two-dimensional (2D) monolayer culture system from human iPSC-derived intestinal organoids [ 25 ]. Cells seeded in a cell culture insert from iPSC-derived intestinal organoids formed a villus structure toward the upper air-side, which improved the versatility for experimental manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they will potentially model human tissue functionality and physiology more accurately than animal models or 2D models ( Lancaster and Knoblich, 2014 ; Kim J. et al, 2020 ). For instance, when sufficiently matured, human intestinal organoids recapitulate budding crypt and villi domains, harbouring proliferative ISCs and progenitors, as well as differentiated enterocytes, goblet cells and Paneth cells, respectively ( Onozato et al, 2021 ). Although organoids contain differentiated cell types, they can be cryopreserved and expanded relatively rapidly ( Clinton and McWilliams-Koeppen, 2019 ).…”
Section: Intestinal Organoids As An Improved Model To Study Intestina...mentioning
confidence: 99%
“…Nevertheless, the directed differentiation process of PSCs towards intestinal organoids takes quite some time (2–3 months), after which hIOs still largely resemble fetal intestinal homeostasis ( McCracken et al, 2011 ; Frum and Spence, 2021 ). Though recently, Onozato and colleagues described a method to enhance organoid maturation in vitro , generating crypt-like budding and expression of villin1 ( Onozato et al, 2021 ). Conversely, enteroids do not have to undergo sequential differentiation steps and can therefore be generated much more rapidly.…”
Section: Pluripotent Stemcell-derived Human Intestinal Organoids Vs T...mentioning
confidence: 99%
“…Potentially significant advantages of this approach include (1) bypassing the reliance on the highly variable spontaneous spheroid production and detachment step during the early stages of organoid formation, and (2) the potential for progenitors to be cryopreserved before aggregation and organoid formation, facilitating the production of banks of organoid precursors that can be accessed without maintaining hPSCs in culture. Several studies have reported utilization of the patterned MHE monolayer to generate HIOs ( Forbester et al., 2015 ; Onozato et al., 2018 , 2021 ; Yoshida et al., 2020 ). However, none of these studies compared the resulting HIOs to those arising spontaneously from multiple hPSC lines, investigated whether MHE can be cryopreserved, banked, and thawed for subsequent HIO generation, nor translated forced aggregation more broadly to other gastrointestinal (GI) organoid types.…”
Section: Introductionmentioning
confidence: 99%